Pengaruh Tuntutan Pekerjaan dan Coping terhadap Work Engagement yang Dimediasi Kepuasan Kerja pada Sumber Daya Perempuan PT. Telekomunikasi Indonesia Regional V Surabaya - DWI RAHAYU, MELIA; SURJANTI, JUN (Jurnal Ilmu Manajemen (JIM), 2018)
Human resources are the main factors must be considered in the effort to maintain and develop the company.Human resources are separate based on gender, male and female. Female employees have job demands andresponsibilities that are equal to male employees in the workplace. In accordance with the nature of femaleemployees have "dual career" that is role as housewife in family and worker at workplace. So, female employeesmust have a good coping to confront and overcome all the demands that exist in her life so the demands do not givea negative effect on life and created a good work engagement in the workplace. The purpose of this study is examineand analyze the influence of job demands and coping of work engagement mediated job satisfaction at femaleemployees on PT. Telekomunikasi Indonesia Regional V. This research uses a quantitative approach obtained byobservation, interview and spread questionnaires. The sample used in this study amount to 65 female employees atPT. Telekomunikasi Indonesia Regional V obtained using saturated sampling technique. Data analysis wasperformed using Partial Least Square (PLS) analysis technique with SmartPLS 3.0. The results of this study indicatethat job demands and coping no significant effect directly to work engagement. However, job satisfaction is able tomediate the influence between job demands and coping of work engagement in order to obtain positive andsignificant results on the indirect influence between job demands and coping of work engagement.Keywords : job demands, coping, work engagement, job satisfaction.